2004
DOI: 10.1143/jjap.43.4031
|View full text |Cite
|
Sign up to set email alerts
|

Application of Laser Scan Lithography to Fabrication of Microcylindrical Parts

Abstract: Laser scan lithography on fine cylindrical specimens is investigated, and various microparts are fabricated successfully by etching the specimens masked by resist patterns. First, the uniform coating of resist films on fine cylindrical specimens is investigated, and a new method is developed. In the new method, the specimen is dipped vertically in the resist bottle, and the bottle is moved downward. Although the coating thickness of PMER P AR-900 varies from 1.5 to 28 mm depending on the material and the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…Each resist was coated using the dip method [8]. Resist thicknesses were controlled by changing the relative draw-up speed, as shown in Fig.…”
Section: Choice Of Resistmentioning
confidence: 99%
See 2 more Smart Citations
“…Each resist was coated using the dip method [8]. Resist thicknesses were controlled by changing the relative draw-up speed, as shown in Fig.…”
Section: Choice Of Resistmentioning
confidence: 99%
“…To answer the requirement, various researches on developing lithography systems for replicating or delineating patterns on cylindrical materials were carried out [1][2][3][4][5][6][7]. The authors also developed laser-scan exposure systems onto fine wires and pipes with diameters of 40-500 µm [8][9][10][11][12][13]. It was demonstrated that very precise patterns were arbitrarily delineated on surfaces of such very fine cylindrical materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, pattern formation has been performed by photolithography on a cylindrical surface, by exposing a resist to laser [11] or electron beam [12] radiation, producing the pattern without employing a mask. However, a single layer is obtained in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…Here, a new resist coating mechanism and a new exposure system are developed [1,2], and etching conditions are investigated. As a result, micro-parts finer than those fabricated by the other method [3,4] are obtained.…”
Section: Introductionmentioning
confidence: 99%